2005
DOI: 10.1128/jcm.43.2.539-545.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Variable-Number Tandem-Repeat Loci in Leptospira interrogans Sensu Stricto

Abstract: Leptospira interrogans sensu stricto is responsible for the most frequent and severe cases of human leptospirosis. The epidemiology and clinical features of leptospirosis are usually associated with the serovars and serogroups of Leptospira. Because of the difficulties associated with serological identification of Leptospira strains, we evaluated a novel PCR-based method for typing L. interrogans serovars. Based upon the genome sequence of L. interrogans serovar Lai type strain 5660, 44 loci were analyzed by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
0
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(146 citation statements)
references
References 23 publications
(26 reference statements)
5
119
0
9
Order By: Relevance
“…In this study, we characterized the isolates at the serogroup level and were unaware if each cluster represented a serovar. A previous study demonstrated that MLVA for L. interrogans was useful for identifying serovars (Majed et al, 2005), whereas other studies indicated considerable diversity of genotypes defined by MLVA within the same serovar (Slack et al, 2006;Zuerner & Alt, 2009). We performed MLVA on 25 serovar strains and compared their profiles with those of the isolates (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we characterized the isolates at the serogroup level and were unaware if each cluster represented a serovar. A previous study demonstrated that MLVA for L. interrogans was useful for identifying serovars (Majed et al, 2005), whereas other studies indicated considerable diversity of genotypes defined by MLVA within the same serovar (Slack et al, 2006;Zuerner & Alt, 2009). We performed MLVA on 25 serovar strains and compared their profiles with those of the isolates (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…MLVA was performed using 11 loci: variable number tandem repeat (VNTR)-4, -7, -10 (Salaün et al, 2006), -19 (Majed et al, 2005), -23 (Zuerner & Alt, 2009), -31 (Majed et al, 2005), -27, -29, -30, -36 and -51 (Slack et al, 2006 for the isolates. The 25 Leptospira serovar strains were also subjected to MLVA as reference.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MLVA typing was done using two sets of oligonucleotides specifi c for the species Leptospira interrogans, L. borgpetersenii and L. kirschneri. The loci VNTR4, VNTR7, VNTR9, VNTR10, VNTR19, VNTR23 and VNTR31 were used to discriminate L. interrogans strains (MAJED et al, 2005) and VNTR4, VNTR7, VNTR10, LB4 and LB5 were used to L. kirschneri, L. borgpetersenii and L. interrogans (SALAÜN et al, 2006). The fi nal volume (50µL) of each reaction mixture containing RCP buffer (20mM Tris-HCL, pH 8.4, 50mM of KCl), 200µm of deoxinucleoside triphosphates, 2µm of each corresponding primer, 2mM of MgCl2, 1.25U of Taq DNA polymerase (Invitrogen) and 5uL of DNA model.…”
Section: Methodsmentioning
confidence: 99%
“…From the DNA formers used in the typing procedures MLVA performed with the primers described by MAJED et al (2005) and SALAÜN et al (2006), 100µL from the culture sample were incubated at 100°C during 10 minutes. The MLVA typing was done using two sets of oligonucleotides specifi c for the species Leptospira interrogans, L. borgpetersenii and L. kirschneri.…”
Section: Methodsmentioning
confidence: 99%